2006
DOI: 10.1037/1528-3542.6.4.622
|View full text |Cite
|
Sign up to set email alerts
|

Sustained and transient modulation of performance induced by emotional picture viewing.

Abstract: We investigated how viewing task-irrelevant emotional pictures affects the performance of a subsequent non-emotional visual detection task. Subjects performed target-detection trials following the offset of individual unpleasant, pleasant and neutral pictures. Sustained interference occurred when subjects viewed blocked unpleasant pictures (mutilated bodies). Such slowing down of reaction time appeared to "build up" with time, consistent with the instatement of a defensive emotional state. With a randomized pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
75
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 52 publications
13
75
0
2
Order By: Relevance
“…The current results replicate previous findings confirming the validity of the picture-viewing paradigm to modulate physiological and behavioral reactions (Bradley et al, 1996;Lang et al, 1993;Low et al, 2008;Oliveira et al, 2009;Pereira et al, 2006;Sarlo et al, 2002). Heart rate responses varied as a function of picture valence.…”
Section: Discussionsupporting
confidence: 91%
“…The current results replicate previous findings confirming the validity of the picture-viewing paradigm to modulate physiological and behavioral reactions (Bradley et al, 1996;Lang et al, 1993;Low et al, 2008;Oliveira et al, 2009;Pereira et al, 2006;Sarlo et al, 2002). Heart rate responses varied as a function of picture valence.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, de Oliveira et al (2012) demonstrated that the amplitude of the readiness potential, which is an electrophysiological marker of motor preparation, is modulated by emotion; these authors suggested that emotionally laden stimuli recruit a pre-set motor repertoire that is consistent with the valence of the stimuli. These studies lend support to the concept that emotional stimuli modulate motor output and our previous studies using aversive pictures are consistent with this idea (Pereira et al, 2004, 2006, 2010; Souza et al, 2012). …”
Section: Discussionsupporting
confidence: 86%
“…Pereira et al (2004, 2006) showed that viewing pictures of mutilated bodies increased RTs in performing a simple non-emotional visual detection task. This interference effect was accompanied by enhanced activity of the entire circuit involved in the task when presenting mutilated bodies compared to neutral pictures (Pereira et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, subjects exhibit fast, involuntary responses to emotional stimuli, such as faces with fearful expressions or aversive pictures (Globisch et al, 1999). In addition, negative stimuli appear to be a more effective source of involuntary interference to on-going tasks than neutral or positive ones (Hartikainen et al, 2000;Tipples and Sharma, 2000;Pereira et al, 2006), and to more readily recruit attention (Bradley et al, 1997;Eastwood et al, 2001). Enhanced visual processing of affective information is also suggested by neuroimaging data.…”
Section: Introductionmentioning
confidence: 89%